2015
DOI: 10.1177/0271678x15608393
|View full text |Cite
|
Sign up to set email alerts
|

O-linked β-N-acetylglucosamine modification of proteins is activated in post-ischemic brains of young but not aged mice: Implications for impaired functional recovery from ischemic stress

Abstract: To evaluate the effect of age on the response of brains to an ischemic challenge, we subjected young and aged mice to transient forebrain ischemia, and analyzed the heat shock response and unfolded protein response, ubiquitin conjugation and SUMO conjugation, and O-linked b-N-acetylglucosamine modification of proteins (O-GlcNAcylation). The most prominent age-related difference was an inability of aged mice to activate O-GlcNAcylation. Considering many reports on the protective role of O-GlcNAcylation in vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 16 publications
2
49
0
Order By: Relevance
“…Global SUMOylation, particularly SUMO2/3 conjugation, and ubiquitination were significantly increased in the brain after CA/CPR (Figure 3B), similar to our previous findings using a forebrain ischemia model 7. In contrast to SUMOylation, ubiquitination did not decrease, even at 24 hours’ reperfusion (Figure 3B).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Global SUMOylation, particularly SUMO2/3 conjugation, and ubiquitination were significantly increased in the brain after CA/CPR (Figure 3B), similar to our previous findings using a forebrain ischemia model 7. In contrast to SUMOylation, ubiquitination did not decrease, even at 24 hours’ reperfusion (Figure 3B).…”
Section: Resultssupporting
confidence: 89%
“…Notably, GRP78, a major component of the activating transcription factor 6 UPR branch, was not increased in aged brains, but was increased ≈2‐fold in young brains (Figure 6B). In a previous study, we found that activation of O‐GlcNAcylation is severely impaired in aged compared with young brains at 1 hour reperfusion after forebrain ischemia 7. Herein, this impairment was still evident at 3 hours’ reperfusion after CA/CPR (Figure 6C).…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations